Comparison of the Effectiveness of Providing Blanket Warmers, Warm Parenteral Fluids, and Operating Room Temperature Modification in Preventing Perioperative Hypothermia - Purwadadi, I Kadek; Agustini, Ni Luh Putu Inca Buntari; Nuryanto , I Kadek; Putri, Ni Made Manik Elisa (Babali Publisher, 2025)
Introduction: Perioperative hypothermia can cause various adverse physiological effects if not prevented. Preventing perioperative hypothermia includes using a blanket warmer, warm parenteral fluid, and operating room temperature modification. The research aimed to compare the effectiveness of blanket warmer, warm parenteral fluid, and operating room temperature modification in preventing perioperative hypothermia. Method: The research design was a true experiment with a posttest-only control design approach. The sample size was 47 for each group, with 188 samples used for the four groups (warmer blanket, warm parenteral fluids, room-modified temperature, and control). This study employed a simple random sampling technique. The instruments used included Standard Operating Procedures (SOP) and an axillary thermometer. The data was collected by filling out an observation sheet, which included observations—and data analysis using the Kruskal-Wallis test. Results: The highest average in preventing hypothermia was observed in the group with operating room temperature modification, with a value of 136.84. The second highest was the blanket warmer group, with an average of 95.59, followed by the warm parenteral fluid group, with an average of 87.20. The control group had the lowest average at 58.3. Conclusion: The group with operating room temperature modification showed a significant difference from the other groups, indicating that this intervention is more effective in preventing perioperative hypothermia.